Non-Contact Boxing and Chronotropic Incompetence in Parkinson’s Disease - Benevides Panassollo, Tone Ricardo (Auckland University of Technology, 2025)
Non-contact boxing training (NCBT) is a recent addition to exercise interventions suitable for people with Parkinson's disease (PwPD). Although NCBT is considered a form of high-intensity interval training (HIIT) for PwPD, it has not been verified as such in this population. This is especially the case if autonomic disturbance, in particular chronotropic incompetence (CI) is present. CI attenuates heart rate (HR) response during aerobic exercise despite increasing demand, thereby limiting the potential for high-intensity zone training. The primary question underpinning this thesis examines this issue and asks whether PwPD can train at high intensity when undertaking NCBT. A second, related question concerns the influence of CI on cardiac and metabolic responses during HIIT and the implications of this for monitoring exercise intensity. The first study in this programme of research is a narrative review of aerobic exercise protocols for PwPD. The review concludes that although the effect of exercise intensity on aerobic performance in PwPD is positive overall, there is inconsistency in reporting training protocols (including lack of agreement around the definition and use of training zones) which limits generalisability, study replication and understanding the mechanisms causing any observed effect. A standardised approach is recommended to optimise outcome. A second finding is that CI appears to have a marked effect on aerobic performance and further research is required to enhance understanding of the phenomenon. This body of work then informed an exploratory study examining the impact of CI on HR and metabolic responses and exercise intensity profiles during a cardiopulmonary exercise test (CPET) in PwPD with and without CI, and age-matched controls. HR and metabolic responses during CPET were significantly attenuated for the CI group, suggesting the need to first classify participants for CI prior to programming aerobic training protocols, and to monitor response throughout training. The third study incorporates individualised physiological measures of exercise intensity obtained from the CPET study to investigate the effect of CI on physiological and clinical responses during NCBT. The results show that PwPD who present with CI, exhibit lower HR responses during NCBT than PD non-CI and controls. However, PwPD with and without CI do meet high-intensity training criteria and spend significant time exercising at and above the threshold zone. In conclusion, this thesis highlights the need for consideration of autonomic dysfunction, in particular CI, when administering aerobic training programmes for PwPD. The results also show that despite attenuated HR and metabolic responses, people with CI are able to exercise in high-intensity zones during NCBT. There is a need for comprehensive reporting of aerobic training protocols for PwPD and the adoption of standardised thresholds for training zones.